SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/134473-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Induced Changes in Oilwell Cements Under Downhole Conditions: First Experimental Results

Abstract: One of the major technological issues for CO 2 injection (for EOR, CCS, etc.) is the long-term behavior of cement-based materials used to ensure the overall sealing performance of the storage wells. When water is present, the CO 2 after injection can react chemically with the cement (i.e. carbonation). How do the CO 2 -enriched formation fluids changes the cement's chemistry and properties? Could the sealing efficiency of the wells be affected by these changes?The objectives of our experimental program are to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…To gather information about the reaction kinetics and phenomenological changes in the cement, Garnier et al, (2010) reported an experiment with two sets of samples. One was neat Class G cement tested at a temperature of 90⁰C and a pressure of 8 MPa for a period of 90 days whilst the second sample was composited of Class G cement containing silica flour (35% BWOC).…”
Section: IVmentioning
confidence: 99%
“…To gather information about the reaction kinetics and phenomenological changes in the cement, Garnier et al, (2010) reported an experiment with two sets of samples. One was neat Class G cement tested at a temperature of 90⁰C and a pressure of 8 MPa for a period of 90 days whilst the second sample was composited of Class G cement containing silica flour (35% BWOC).…”
Section: IVmentioning
confidence: 99%
“…This standard was chosen as it is commonly used in the industry for the preparation of primary and secondary cement. Different researchers (e.g., Barlet-Gouedard et al, 2006Kutchko et al, 2007Kutchko et al, , 2008Garnier et al, 2010;Brandl et al, 2010;Lesti et al, 2012;Zhang et al, 2014) also used the API standard for the preparation and testing of the oil well cement. The detailed instruction of the cement preparation and testing procedures used in this paper are given in the API 10-A and 10-B.…”
Section: Sample Preparationmentioning
confidence: 99%